2017
DOI: 10.1210/jc.2017-00822
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Insulin Action by an Allosteric Insulin Receptor Antibody in Healthy Volunteers

Abstract: Single X358 infusions were well tolerated and resulted in a dose-dependent reduction in insulin sensitivity. Clinical development of X358 in hyperinsulinemic, hypoglycemic conditions is proceeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…7 In healthy volunteers, a single dose of XMetD resulted in a significant elevation of postprandial plasma glucose concentration and a significant attenuation of the decrease in plasma glucose induced by insulin in the setting of an insulin tolerance test. 8 Our study extends these findings in a mouse model relevant to the human condition of endogenous hyperinsulinemic hypoglycemia. Although SUR-1 ¡/¡ mice are relatively normoglycemic in the fed state, 9,10 they develop hypoglycemia with fasting, which allowed us to test the potential for an insulin receptor allosteric inhibitor to normalize fasting plasma glucose in the absence of functional K ATP channels.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…7 In healthy volunteers, a single dose of XMetD resulted in a significant elevation of postprandial plasma glucose concentration and a significant attenuation of the decrease in plasma glucose induced by insulin in the setting of an insulin tolerance test. 8 Our study extends these findings in a mouse model relevant to the human condition of endogenous hyperinsulinemic hypoglycemia. Although SUR-1 ¡/¡ mice are relatively normoglycemic in the fed state, 9,10 they develop hypoglycemia with fasting, which allowed us to test the potential for an insulin receptor allosteric inhibitor to normalize fasting plasma glucose in the absence of functional K ATP channels.…”
Section: Discussionsupporting
confidence: 68%
“…7 In a Phase 1 clinical study, a single infusion of XMetD resulted in a dosedependent reduction in insulin sensitivity in healthy adults. 8 We have now examined the effect of XMetD on fasting plasma glucose and other parameters of glucose and energy metabolism in a mouse model of K ATP HI, the SUR-1 ¡/¡ mice. 9,10 initiation of treatment, including body weight, fasting and fed plasma glucose and fasting plasma insulin, followed by randomization to treatment with XMetD or control antibody (KLH2G2) ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…A number of new therapeutic developments are likely to improve treatment options for CHI in the near future. In addition to soluble glucagon formulations currently in trial, other products in development include a monoclonal antibody that is a negative allosteric modulator of the insulin receptor which reduces insulin's action on glucose . The glucagon‐like peptide‐1 (GLP‐1) receptor is also a putative target with potential to reduce insulin secretion as evidenced by a drug trial of exendin 9‐39 in older children and adults .…”
Section: Other Medicationsmentioning
confidence: 99%
“…With therapeutic humanized monoclonal antibodies now well established as treatments both for cancer and noncancer indications ( 9 ), interest in biological therapies targeting the INSR has been recently rekindled. Inhibitory INSR antibodies are now in phase 1 human trials ( 10 ), while stimulatory antibodies have been shown to ameliorate diabetes in rodents ( 11 13 ) and primates ( 14 ). Given the high clinical need in recessive insulin receptoropathy, we previously assessed the effect of monoclonal anti-INSR antibodies ( 15 19 ) on a series of disease-causing mutant INSRs in cell culture models, corroborating and extending prior findings by demonstrating an action of antibodies against a panel of mutant receptors ( 20 ).…”
Section: Introductionmentioning
confidence: 99%